Performance of oat (Avena sativa) genotypes under alkali soil irrigated with sodic water* - SHARMA, P C; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at the farmer’s field during winter (rabi) 2003-04 to study the effect of gypsum application (2 and 4 tonnes/ha) on 5 oat varieties in a moderately alkali soil (pH 9.3) irrigated with alkali water. Gypsum application did not significantly influence the green forage yield and crude protein content of 5 oat genotypes. Among the 5 genotypes, ’JHO 2000-6’ performed better under alkali soil irrigated with alkali water by recording highest green forage yield besides highest Na:K and lowest K accumulation.